Hypothenar Hammer syndrome: importance of MR and conventional angiographic findings - Geng, Meng; Singh, Tanveer (Journal of Xiangya Medicine, 2017)
Hypothenar Hammer syndrome (HHS) is a rare diagnosis characterized by ulnar insufficiency, often accompanied by ulnar nerve neurologic deficit. This syndrome is caused by repetitive trauma to the ulnar artery in the Guyon’s or ulnar canal, causing arterial intimal dissociation with possible aneurysmal formation, vasospasm, or even thrombosis. Hypothenar hammer syndrome is often suspected clinically using Allen’s test, which is a sensitive but nonspecific test. Ultrasound can be used for initial evaluation; however conventional angiography has been the gold standard for diagnosis. Conventional angiographic findings include classic tortuous, corkscrew appearance of the ulnar artery. MR angiography is frequently used as a noninvasive imaging modality and has an advantage of multiplanar imaging, high soft tissue contrast, as well as lack of ionizing radiation. Accurate diagnosis of this syndrome is important to distinguish hypothenar hammer syndrome from other similar clinical entities such as Raynaud's phenomenon in order to appropriately treat this condition. This entity should be kept in mind when a cardiac patient with certain occupational hazards has to undergo radial artery access for catheterization. Management of hypothenar hammer syndrome is currently debated, though most commonly is treated conservatively, with or without added surgical management.